2020
DOI: 10.21037/atm-20-5947
|View full text |Cite
|
Sign up to set email alerts
|

Application of an elevated plasma D-dimer cut-off value improves prognosis prediction of advanced non-small cell lung cancer

Abstract: Background: Tumor-related coagulation dysfunction has been reported to be closely associated with poor prognosis. The present study is aimed to evaluate the prognostic prediction of an elevated plasma D-dimer cut-off value in advanced non-small cell lung cancer (NSCLC).Methods: A total of 233 patients initially diagnosed with advanced NSCLC were retrospectively analyzed, an elevated plasma cut-off value 981 ng/mL of D-dimer, which was instead of the clinical cut-off value 500 mg/mL, was used to determine the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 29 publications
(30 reference statements)
1
13
0
1
Order By: Relevance
“…Chen et al found that increasing the threshold value of D-dimer from 0.5 to 0.981 µg/mL was statistically significant across different age groups ( 54 ). They concluded that the cut-off value of 0.5 µg/mL could not reflect the correlation between age and D-dimer.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al found that increasing the threshold value of D-dimer from 0.5 to 0.981 µg/mL was statistically significant across different age groups ( 54 ). They concluded that the cut-off value of 0.5 µg/mL could not reflect the correlation between age and D-dimer.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor microenvironment constituted by immune cells and stromal cells with other “niche” cells leads to cancer patients' tumor‐associated coagulation abnormalities, which increases plasma D‐dimer concentration, one of the fibrin degradation products. Furthermore, D‐dimer is associated with lymph node metastases in NSCLC 37 . This meta‐analysis points out that the plasma D‐dimer value was significantly higher in lung cancer patients (SMD 3.10; 95% CI 2.08–4.12; p = 0.000) when compared with the control group using seven studies.…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, D-dimer is associated with lymph node metastases in NSCLC. 37 This meta-analysis points out that the plasma D-dimer value was significantly higher in lung cancer patients (SMD 3.10; 95% CI 2.08-4.12; p = 0.000) when compared with the control group using seven studies. The single-arm meta-analysis on seven studies with a total of 1488 lung cancer patients and 328 control groups revealed that the pooled D-dimer was 275.99 (95% CI:172.9-11735.9) as compared with the control group 0.2 (95% CI:0.20-0.37).…”
Section: Discussionmentioning
confidence: 90%
“…D-dimer and fibrinogen levels were the coagulation indicators that correlated with cancer prognosis; they also correlate with patient prognosis in non-small cell lung cancer, 19 esophageal cancer, 20 and gastrointestinal cancer. 21 However, this has not been adequately studied in thymic epithelial tumors.…”
Section: Introductionmentioning
confidence: 96%
“…16 Conventional biochemical markers, such as LDH and CRP, have been reported to be valuable prognostic biomarkers in thymic epithelial tumors 17,18 ; however, the prognostic value of other biochemical markers related to liver function has not been demonstrated. D-dimer and fibrinogen levels were the coagulation indicators that correlated with cancer prognosis; they also correlate with patient prognosis in non-small cell lung cancer, 19 esophageal cancer, 20 and gastrointestinal cancer. 21 However, this has not been adequately studied in thymic epithelial tumors.…”
Section: Introductionmentioning
confidence: 96%